ANALISIS PAPARAN NITRAT PADA AIR MINUM DAN DAMPAKNYA TERHADAP METEMOGLOBINEMIA SERTA AFINITAS OKSIGEN HEMOGLOBIN - Firdus Firdus (J-KESMAS: Jurnal Kesehatan Masyarakat, 2026)
Nitrates are one of the chemical contaminants often found in drinking water sources, especially in areas with intensive agricultural activity involving the use of nitrogen fertilizers. High concentrations of nitrates in drinking water can have health effects on humans. In the body, nitrates can be reduced to nitrites by microorganisms in the digestive tract. Nitrites can then oxidize hemoglobin into methemoglobin, which is unable to bind oxygen effectively, thereby causing methemoglobinemia and decreasing hemoglobin oxygen affinity. This condition has the potential to disrupt oxygen transport in the blood and may cause tissue hypoxia, especially in vulnerable groups such as infants and children. This study aims to analyze the toxicological relationship between nitrate exposure in drinking water and the risk of methemoglobinemia and decreased hemoglobin oxygen affinity. The method used in this study is a literature review of various scientific articles and research journals relevant to nitrate toxicity, the mechanism of methemoglobin formation, and its impact on the oxygen transport system in the blood. The results of the study show that exposure to high concentrations of nitrate can increase the formation of methemoglobin in the blood, thereby interfering with the ability of hemoglobin to bind and distribute oxygen to body tissues. Therefore, monitoring the quality of drinking water is essential to prevent the occurrence of methemoglobinemia and reduce the risk of oxygen affinity loss in hemoglobin.